Financial Literacy Series: Financial Planning For Families in TK/POS PAUD Pandanwangi, Bandung City - Kartawinata, Budi Rustandi; Wardhana, Aditya (Journal of Community Service and Society Empowerment, 2025)
This study presents a community service initiative aimed at enhancing financial literacy among families associated with TK/POS PAUD Pandanwangi in Bandung City. Recognizing the critical role of financial planning in improving family financial well-being, the program targeted both parents and educators to foster responsible financial behavior from early childhood education settings. Employing a qualitative method, the program was conducted in two phases: planning through collaborative engagement with the community, and implementation through workshops and seminars addressing topics such as budgeting, saving, investment, and online gambling awareness. A total of 28 participants attended the session, and post-event evaluation revealed that 82% demonstrated improved understanding of financial planning principles. The findings highlight the effectiveness of tailored, community-based financial education in promoting economic empowerment. This initiative underscores the importance of integrating financial literacy into early education and the need for systemic support to ensure sustainable financial inclusion.